On the Romanian endemic species of Salvia (Lamiaceae) and its natural hybrids: nomenclatural and taxonomic aspects - Nachychko, Viktor O.; Sosnovsky, Yevhen V. (Phytotaxa, 2020)
Salvia transsylvanica is regarded to be endemic to the Transylvanian Basin, Eastern and Southern Carpathians in Romania. In natural habitats, it easily intercrosses with other sage species, such as S. nemorosa, S. nutans, and S. pratensis, with the hybrids described as nothospecies S. ×hybrida, S. ×telekiana, and S. ×bichigeanii, respectively. One specimen from GOET is designated here as a lectotype of S. pratensis var. transsylvanica, the basionym of S. transsylvanica. In addition, three specimens from LW, BP, and BUCA are designated as the lectotypes for hybrid names. Main diagnostic features of S. transsylvanica, its hybrids, and respective second parental species are compared and discussed.